Ti3C2 MXene as a new nanofiller for robust and conductive elastomer composites. Issue 31 (25th July 2019) - Li, Qunyang; Zhong, Bangchao; Zhang, Wenqiang; Jia, Zhixin; Jia, Demin; Qin, Si; Wang, Jing; Razal, Joselito M.; Wang, Xungai
Abstract : Ti3 C2 MXene with a layered 2D structure was applied as a novel functional filler in rubber for the first time. Abstract : Ti3 C2 MXene with a layered 2D structure was applied as a novel functional filler in rubber for the first time. A facile and green method was proposed to fabricate rubber/Ti3 C2 nanocomposites via a freeze-drying & mechanical mixing process. It was found that Ti3 C2 with ∼1 nm thickness fabricated by etching Al from Ti3 AlC2 phases can be dispersed in styrene-butadiene rubber (SBR) evenly in a single-layered state. Mechanical strength and electrical and thermal conductivities of the rubber nanocomposites were remarkably enhanced by the incorporation of Ti3 C2, showing dramatic improvement compared with reduced graphene oxide (rGO) reinforced rubber composites. For example, the thermal conductivity of SBR nanocomposites with 3 wt% rGO was 0.265 W m −1 k −1, while that of SBR nanocomposites with only 1.96 wt% Ti3 C2 reached 0.477 W m −1 k −1 . Meanwhile, the resistance of rubber/Ti3 C2 nanocomposites was stable under complex deformation and their sensitivity was well recovered during stretching/shrinking cycles under large strain. Moreover, it was discovered that incorporating Ti3 C2 in rubber nanocomposites dramatically improved the wet skid resistance and thermal stability without increasing the rolling resistance. Ti3 C2 MXene with a distinctive structure and properties as well as uniform dispersion will have more potential for the preparation of high-performance rubber nanocomposites, especially for green tires and flexible sensors.